Terorisme, perang global, dan masa depan demokrasi - Soerjadi, Trimoelja D. (Trimoelja Darmasetia), 1939- (Depok : Matapena, 2004)
On terrorism and Indonesian legal instruments to fight from terror attacks.
Includes index.
Keywords: Terrorism -- Indonesia; Terrorism